EA15, MIR22, LINC00472 as diagnostic markers for diabetic kidney disease. Issue 6 (14th October 2018) - Wang, Yan‐Zhe; Zhu, Ding‐Yu; Xie, Xin‐Miao; Ding, Miao; Wang, Yong‐Lan; Sun, Lin‐Lin; Zhang, Nan; Shen, E.; Wang, Xiao‐Xia
Abstract: This study aimed to investigate the molecular mechanisms of diabetic kidney disease (DKD) and to explore new potential therapeutic strategies and biomarkers for DKD. First we analyzed the differentially expressed changes between patients with DKD and the control group using the chip data in Gene Expression Omnibus (GEO) database. Then the gene chip was subjected to be annotated again, so as to screen long noncoding RNAs (lncRNAs) and study expression differences of these lncRNAs in DKD and controlled samples. At last, the function of the differential lncRNAs was analyzed. A total of 252 lncRNAs were identified, and 14 were differentially expressed. In addition, there were 1, 629 differentially expressed messenger RNAs (mRNAs) genes, and proliferation and apoptosis adapter protein 15 ( PEA15 ), MIR22, and long intergenic nonprotein coding RNA 472 ( LINC00472 ) were significantly differentially expressed in DKD samples. Through functional analysis of the encoding genes coexpressed by the three lncRNAs, we found these genes were mainly enriched in type 1 diabetes and autoimmune thyroid disease pathways, whereas in Gene Ontology (GO) function classification, they were also mainly enriched in the immune response, type I interferon signaling pathways, interferon‐γ mediated signaling pathways, and so forth. To summary, we identified EA15, MIR22, and LINC00472 may serve as the potential diagnostic markers of DKD. Abstract : We identified EA15, MIR22, and LINC00472 may serve as the potential diagnostic markers of diabetic kidney disease.